НОВЕЛИ У ПРАВОВОМУ РЕГУЛЮВАННІ ДЕРЖАВНИХ ЗАКУПІВЕЛЬ - Nekrasova, T.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper traces the changes in the legal regulation of economic relations in the sphere of government purchases in Ukraine. Theoretical and practical problems concerning realization of corresponding norms according to the legislation of the Russian Federation are considered. The regulative influence of the state on the activity of economic subjects through government purchases is studied. The proposals on making changes in some provisions of the legislation are offered to improve the procedure of purchases.